Analisis Dampak Negatif Penggunaan Handphone Terhadap Anak SD - Faisal Yajid (Universitas Palan, 2023)
Mobile is an electronic device that is used by many people. Many people already have cell phones, even from an early age to the elderly, all of them already have cell phones and they already know how to use them. Besides that, cellphones have lots of benefits that can be used, we can play games, play Facebook, play Instagram, play tiktok and etc. We can also reach the whole world by using a cellphone and can search for all activities in the world with 1 cellphone. However, my current goal is to research more deeply about analyzing the negative impact of using mobile phones on elementary school children. This research uses a qualitative method, why did I take a qualitative method because in this research there are case studies. The results of this study are that many parents buy cellphones for their children who are still in elementary school and on average children use cellphones to play games, watch YouTube, even these children can access 18+ sites. What should have happened, the role of parents at that time was very important to control the development of their children so that they were kept away from negative things about cellphone use. However, from the cases that are currently rampant, the role of parents in educating their children who are still in elementary school does not pay much attention, even parents allow them to be free to play mobile phones whenever and wherever. With this the negative impact on the child will begin to be seen as an example: the child will be lazy to learn about school, the child will be difficult to manage, the child will be cranky when what he wants is not carried out, the child will plunge into the world of the internet where he will access the web in terms of negative and the worst thing is that when the child uses a cellphone excessively he will experience blur in his eyes and the child when he is an adult will use minus glasses